Faktor-Faktor yang Mempengaruhi Rendahnya Penggunaan Metode Kontrasepsi Jangka Panjang (MKJP) di Puskesmas Sungai Pinang Kabupaten Ogan Ilir Tahun 2023 - Novriyani, Anggia; Wathan, Fika Minata; Sari, Intan; Hamid, Siti Aisyah (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2025)
The increasing incidence of maternal deaths and unplanned pregnancies are still global reproductive health problems in developing countries. This problem is greatly influenced by the lack of use of contraceptives. The research aims to determine the factors that influence the low use of long-term contraceptive methods at the Sungai Pinang Community Health Center, Ogan Ilir Regency in 2023. This research design uses an analytical survey with a cross sectional method. The population in this study were all acceptors recorded in the active family planning register at the Sungai Pinang Community Health Center from January to December 2023, namely 3485 acceptors. The sample was taken using a purposive sampling technique as many as 93 respondents. The analysis technique uses Univariate, Bivariate (Chi square). Based on the results of the Chi Square statistical test, there is a partial influence between age and the low use of MKJP at the Sungai Pinang Community Health Center, Ogan Ilir Regency in 2023, the Chi-Square results obtained at a significance level of a = 0.05 obtained a p value = 0.022, There is an influence between parity partially with the low use of MKJP at the Sungai Pinang Community Health Center, Ogan Ilir Regency in 2023, Chi-Square results were obtained at a significance level of a = 0.05, with a p value = 0.000. There is a partial influence between education and the low use of MKJP at the Sungai Pinang Community Health Center Ogan Ilir Regency In 2023, a Chi-Square result was obtained at a significance level of a = 0.05, a p value = 0.000. It is hoped that the results of this research can increase the support of health workers in carrying out the duties of Family Planning (KB) services to provide education and counseling in order to realize the rational use of contraception for family planning acceptors so as to minimize unwanted pregnancies and reduce the Maternal Mortality Rate (MMR).